Development of the Nyika Plateau, Malawi: A Long Lived Paleo‐Surface or a Contemporary Feature of the East African Rift?. (8th August 2022) - McMillan, M. F.; Boone, S. C.; Kohn, B. P.; Gleadow, A. J.; Chindandali, P. R.
Abstract: Northern Malawi's Nyika Plateau is a 3, 700 km 2 large, highly elevated (∼2, 500 m) plateau located at the western margin of the Miocene‐Recent Malawi rift and the confluence of multiple Proterozoic orogenic belts. Neighboring asthenospheric upwelling in the Rungwe Volcanic Province, associated with the active East African Rift, has created similar topographic highs, leading some to speculate that the formation of Nyika could be related. Here, we present new low‐temperature data using apatite fission track, apatite (U‐Th‐Sm)/He and zircon (U‐Th)/He thermochronology to constrain the upper crustal thermal history of the Nyika region since the Devonian. The data suggest that Nyika was an isolated feature since at least the Permo‐Triassic, well before more recent rifting in Malawi, and may have developed as a horst between two large Karoo grabens, the Henga‐Ruhuhu and the North Rukuru to the southeast and northwest, respectively. Similarities between the thermal histories of Nyika and the currently separated Livingstone Plateau to the east allow for the possibility that these may have been connected in a contiguous highland prior to the formation of the intervening Neogene Malawi rift. Thermal history models for exposed Precambrian basement samples adjacent to Nyika, and once buried beneath the neighboring Karoo basins, indicate that up to 3.4 km of Permo‐Triassic section has since been eroded, with samples along the plateau not indicating burial of Karoo‐type sediment at this time. Most recent cooling histories suggest that the plateau surface continued to denude at varying degrees from the Cretaceous and reached near‐surface temperatures in the Late Paleogene‐Neogene. Plain Language Summary: Africa is composed of tectonic plates that are pulling apart from the hot upwelling mantle beneath the continent. This is forming a long narrow zone of elevated domes, rift valleys, lakes, and volcanic centers that span 2, 200 km from the Red Sea to Malawi. Rift‐related activity started 40 million years ago and is still active today. The Nyika plateau is a large, elevated plateau located in northern Malawi directly adjacent to active rifting. To the north of Nyika is a large volcanic complex that formed from rising mantle plumes 25 million years ago. Some researchers think that Nyika may have also formed from the same rising mantle that created the volcanoes; however, others think it may be a remnant plateau older than 300 million years. In this study, we use dating techniques sensitive to near‐surface temperatures to find out when the plateau formed. We found that the plateau was a topographic high for at least 250 million years and is not a direct feature of recent rifting. However, the exposed plateau surface is young and has undergone multiple erosion and alteration. We found that Nyika may have been part of an even larger structure that was separated by rifting about 10 million years ago. Key Points: The Nyika Plateau was likely an isolated topographic feature by the Permo‐Triassic and probably not a result of recent active rifting Nyika likely developed as a horst along with the Livingstone Plateau, bound by the Henga‐Ruhuhu and North Rukuru grabens during Karoo rifting Thermal history modeling suggests the region surrounding Nyika has denuded up to 3.4 km of sedimentary cover since the Cretaceous